2022
DOI: 10.1101/2022.06.30.498294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early phyllosphere microbial associations impact plant reproductive success

Abstract: The above-ground plant microbiome (the phyllosphere) is increasingly recognized as an important component of plant health. We hypothesized that phyllosphere interactions may be disrupted in a greenhouse setting, where microbial dispersal is limited, and that adding a microbial amendment might yield important benefits to the host plant. Using a newly developed synthetic phyllosphere microbiome for Tomato, we tested this hypothesis across multiple trials by manipulating microbial colonization of leaves and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…For example, Azomite is lightly weathered, contains short-range-order minerals with aluminosilicates, and its application in the top layer of soil may temporarily create andisol-like conditions. In previous studies with greenhouse-grown tomatoes, Azomite increased tomato production (Mehlferber et al, 2022a; 2022b), and here it was found to promote early seedling growth. These data suggest that the application of volcanic ash fertilizers, like Azomite may increase soil productivity similarly to Andislos.…”
Section: Discussionsupporting
confidence: 74%
“…For example, Azomite is lightly weathered, contains short-range-order minerals with aluminosilicates, and its application in the top layer of soil may temporarily create andisol-like conditions. In previous studies with greenhouse-grown tomatoes, Azomite increased tomato production (Mehlferber et al, 2022a; 2022b), and here it was found to promote early seedling growth. These data suggest that the application of volcanic ash fertilizers, like Azomite may increase soil productivity similarly to Andislos.…”
Section: Discussionsupporting
confidence: 74%
“…At the higher concentration (1 g/L) tested, Azomite reduced cotyledon expansion and hypocotyl growth in etiolated, FRc and PAR-grown seedlings (Figures 6), implying an optimal range (>.1 to <1.0 g/L) of beneficial Azomite activity on Arabidopsis seedlings during deetiolation. Recent experiments performed with greenhouse grown tomatoes have revealed similar relationships between plant growth and Azomite concentrations (Mehlferber et al, 2023). Higher concentrations may result in an increase in growth inhibition, potentially due to currently unknown impacts of excessive nutrient elements like K, as described above (Xu et al, 2020).…”
Section: Possible Mechanisms Of Azomite Activitymentioning
confidence: 85%
“…Figure 1 shows 4-day-old seedlings grown in continuous darkness (Dc), continuous red light (Rc), or continuous white light (WLc). The initial light treatments were selected to assess any observable phenotypic differences in response to Azomite concentrations, which were chosen based on relative amounts used in previous greenhouse tomato trials (Mehlferber et al, 2023).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Microbiomes have strong effects on the health and fitness of their hosts (1,2). Host plant growth and physiology are affected by the presence of leaf-associated (phyllosphere) microbes, with microbial taxa acting as mutualists, commensals, and antagonistic pathogens (3)(4)(5)(6). Phyllosphere microbes live in complex microecosystems (7,8) performing functions that drive plant nutrient acquisition, phytohormone production, and stress tolerance (3).…”
Section: Introductionmentioning
confidence: 99%